Aproximación al estudio de la gestación de sustitución desde la perspectiva del bioderecho - Souto Galván, Beatriz (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2005)
The scientific advances in the field of Genetics and Biology have forced the legislador to adopt concrete legal solutions, generally starting off from certain ethical criteria that, sometimes, enter in conflict with the individual ethics or freedom of conscience. In this respect one of these questions is the so called gestation of substitution. The gestation of substitution has triggered an intense debate in the social, ethical and legal scope, which has reached the present date. In fact there is evidence of such cases of gestation of substitution that generates conflicts of difficult solution, and that they reveal undoubtly the complexity of this phenomenon.
Keywords: Surrogate motherhood; Bioethics; Freedom of conscience